Die opkoms en huidige stand van die Nuwe-Testamentiese ondersoek in Suid-Afrika: Deel 3 - "n Kritiese evaluasie - Toit, Andries Bernardus du (Hervormde teologiese studies, 1994)
The rise and current state of New Testament research in South Africa: Part 3 - A critical evaluation First the pros and cons of the South African emphasis on methodology arw discussed. On the positive side a much greater sensitivity for methodological austerity has been developed. On the negative side New Testament research has not contributed enough towards serving theology and the church at large. In dealing with the problem of relevancy in the socio-political field, it is acknowledged that more should be done, without putting the specific character of New Testament studies in jeopardy. The burning issue of the relationship between faith and reason should be tackled. The correct approach seems to be respecting the tension between these two entities, while at the same time working and striving towards closing the gap between them.